Cost-push and conflict inflation in theory and practice: With a discussion of the Italian case - Davide Romaniello; Antonella Stirati (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
This study contributes to the ongoing discussion surrounding the recent upswing in inflation by presenting an analytical framework and empirically examining inflation trends in Italy. Its primary aim is to unveil the underlying causes, distributive repercussions, and mechanisms through which inflation spreads. We adopt a cost-push and distributive conflict perspective on current inflation. Within this perspective, some contributions argued for a profit-driven inflation, while others dispute this interpretation. They emphasize that increases in profit share or operating surplus, especially amid rising import costs, do not necessarily translate to heightened overall profitability. To disentangle these intricacies, the paper puts forth an analytical framework that clarifies how escalating import costs can elevate profit shares and set in motion inflationary processes, even in the absence of explicit conflicts over income distribution. Turning attention to the Italian context, the study utilizes descriptive statistics, sectoral data, and simple simulations to gain insights into the drivers of inflation and its distributive consequences. Additionally, a Structural Vector Autoregressive (SVAR) model is deployed to uncover the nature and timing of the propagation process. The paper concludes with some policy implications based on the findings.
Keywords: E31; E12; E2; 330; inflation; cost-push; mark-up; distribution; Italian economy